Geochemical characteristics and provenance studies of metasedimentary rocks Kullu-Rohtang Pass-Sissu section of NW Himalaya, India (Journal of Nepal Geological Society, 2000)
The metasedimentary rocks along the Kullu-Rohtang Pass-Sissu section, NW Himalaya, have been analysed geochemically to characterise the composition of their provenance. The studies carried out suggest that, the source for these rocks is mainly of felsic nature, remarkably similar in composition to average Phanerozoic upper continental crust. The deposition of the sediments took place in an oxidising environment, and in a tectonic setting that spans from active to passive continental margins.